Enhanced extracellular production of alpha-lactalbumin from Bacillus subtilis through signal peptide and promoter screening - Yuqi Zhu; Pengdong Sun; Chunjian Li; Yu Zhang; Yu Wang; Jingyuan Li; Yanfeng Liu; Jian Chen; Yang Deng (Food Science and Human Wellness)
Alpha-lactalbumin (α-LA) is a major whey protein found in breast milk and plays a crucial role in the growth and development of infants. In this study, Bacillus subtilis RIK1285 harboring AprE signal peptide (SP) was selected as the original strain for the production of α-LA. It was found that α-LA was identified in the pellet after ultrasonic disruption and centrifugation instead of in the fermentation supernatant. The original strain most likely only produced α-LA intracellular, but not extracellular. To improve the expression and secretion of α-LA in RIK1285, a library of 173 homologous SPs from the B. subtilis 168 genome was fused with target LALBA gene in the pBE-S vector and expressed extracellularly in RIK1285. SP YjcN was determined to be the best signal peptide. Bands in supernatant were observed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and purified by nickel column to calculate the highest yield signal peptide. In addition, different promoters (PaprE, P43, and Pglv) were compared and applied. The results indicated that the strain RIK1285-pBE-Pglv-YjcN-LALBA had the highest α-LA yield, reaching 122.04 μg/mL. This study demonstrates successful expression and secretion of human α-LA in B. subtilis and establishes a foundation for simulating breast milk for infant formulas and developing bioengineered milk.